Does Socioeconomic Development Explain the Association Between Seafood Consumption and Cross-National Homicide?. Issue 3 (August 2018) - Testa, Alexander; Rennó Santos, Mateus; Weiss, Douglas B.
Biological theories of crime propose that neurological benefits from consuming omega-3 fatty acids can reduce aggressive behavior. At the macro level, prior work has found a negative bivariate association between seafood consumption and homicide rates. Using data from a sample of 82 countries, and applying both multivariate regression and structural equation modeling, we find that socioeconomic development simultaneously affects the consumption of seafood and homicide rates, generating a spurious relationship. These findings demonstrate that omitting theoretically relevant variables, as well as inferring macro-level associations from micro-level patterns, can lead to erroneous conclusions regarding support for criminological theories or criminal justice policies.